Discovery of PG545: a highly potent and simultaneous inhibitor of angiogenesis, tumor growth, and metastasis - Ferro, Vito; Harenberg, Job (Journal of medicinal chemistry, 2012)
Increasing the aglycone lipophilicity of a series of polysulfated oligosaccharide glycoside heparan sulfate (HS) mimetics via attachment of a steroid or long chain alkyl group resulted in compounds with significantly improved in vitro and ex vivo antiangiogenic activity. The compounds potently inhibited heparanase and HS-binding angiogenic growth factors and displayed improved antitumor and antimetastatic activity in vivo compared with the earlier series. Preliminary pharmacokinetic analyses also revealed significant increases in half-life following iv dosing, ultimately supporting less frequent dosing regimens in preclinical tumor models compared with other HS mimetics. The compounds also displayed only mild anticoagulant activity, a common side effect usually associated with HS mimetics. These efforts led to the identification of 3β-cholestanyl 2,3,4,6-tetra-O-sulfo-α-d-glucopyranosyl-(1→4)-2,3,6-tri-O-sulfo-α-d-glucopyranosyl-(1→4)-2,3,6-tri-O-sulfo-α-d-glucopyranosyl-(1→4)-2,3,6-tri-O-sulfo-β-d-glucopyranoside, tridecasodium salt (PG545, 18) as a clinical candidate. Compound 18 was recently evaluated in a phase I clinical trial in cancer patients.
Gesehen am 21.09.2018